Synthesis of 3', 4', 5, 6, 7-Pentamethoxy-8-C-Prenylflavone: Synthesis of Pentamethoxy Prenylflavone (Biological Sciences - PJSIR, 2009)
3', 4', 5, 6, 7-Pentamethoxy-8-C-prenylflavone, isolated from the leaves of Malaysian Orthosiphon stamineus, was synthesized starting with treating 2, 4, 5, 6-tetrahydroxyacetophenone with dimethyl sulphate which yielded several other minor compounds as well. The synthesized title compound is identical in all respects with the natural sample.